A Study Through A Butlerian Lens On The ASEAN Intergovernmental Commission On Human Rights’ (AICHR) And Their Ineffectual Role In Protecting Sexual Orientation, Gender Identity And Expression - Arthit , Meemaitree (2016)
This research aims to criticize the role of the ASEAN Intergovernmental Commission on Human Rights (AICHR), that is, the ASEAN’s Human Rights mechanism, in developing protections toward Sexual Orientation, Gender Identity and Expression (SOGIE), especially marriage rights, in this region. Since its formal existence in 2009 via ASEAN member’s ratification, this intergovernmental organization hasn’t provided any programs protecting the human rights of ASEAN peoples. However, Sexual Orientation, Gender Identity and Expression fares much worse because this issue becomes internalized as the particular state’s responsibility, whenever there is an attempt to raise this issue to the international level, by asserting their right to non-interference from AICHR. The biggest constraint for SOGIE is that the state member’s understanding and perception is severely limited by their inability to link SOGIE issues with human rights. Moreover, SOGIE issues are regularly treated as illegal and/or immoral behaviors in many ASEAN states such as Malaysia, Indonesia and Myanmar. These phenomena illustrate that ASEAN state members are still living in the past by interpreting human rights according to the binary dichotomy of the sexes. Hence, Judith Butler’s idea on performativity would be suitable for critiquing this situation. Utilizing a Butlerian lens would show how sex, sexuality and gender is constructed and transformed by society over time. Finally, the study will collect and analyze the data via publications i.e. textbooks, factsheets and journal articles, to support the research’s argument and to represent how states normalize a constructed heterosexuality to the public.